2020
DOI: 10.1371/journal.pone.0240792
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and biomagnification of microplastics in marine organisms: A review and meta-analysis of current data

Abstract: Microplastic (MP) contamination has been well documented across a range of habitats and for a large number of organisms in the marine environment. Consequently, bioaccumulation, and in particular biomagnification of MPs and associated chemical additives, are often inferred to occur in marine food webs. Presented here are the results of a systematic literature review to examine whether current, published findings support the premise that MPs and associated chemical additives bioaccumulate and biomagnify across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(147 citation statements)
references
References 99 publications
5
108
0
9
Order By: Relevance
“…A trophic transfer of microplastic particles between species of different trophic levels can be assumed as this has previously been determined by other studies (Farrell and Nelson, 2013;Setälä et al, 2014;Nelms et al, 2018). In addition, the ingestion and presence of microplastics has been highly studied throughout the food web in recent years (Miller et al, 2020). Besides the unintentional uptake of microplastics by prey species, an intentional uptake by organisms caused by a burdened environment or due to accidental prey resemblance has already been shown (Ory et al, 2017;Roch et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…A trophic transfer of microplastic particles between species of different trophic levels can be assumed as this has previously been determined by other studies (Farrell and Nelson, 2013;Setälä et al, 2014;Nelms et al, 2018). In addition, the ingestion and presence of microplastics has been highly studied throughout the food web in recent years (Miller et al, 2020). Besides the unintentional uptake of microplastics by prey species, an intentional uptake by organisms caused by a burdened environment or due to accidental prey resemblance has already been shown (Ory et al, 2017;Roch et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Reports of microplasticrelated risks for marine organisms have, for the most part, been associated with their uptake, and specifically direct ingestion of microplastic items (GESAMP, 2019). Other pathways, however, such as passive uptake through the gills (Bour et al, 2020a) or via trophic transfer from prey items (Santana et al, 2017;Miller et al, 2020) have been demonstrated in controlled laboratory experiments. Thus, similar to other contaminants (Blanco et al, 2018;Amoroso et al, 2020;Hassell et al, 2020), depuration is a major factor influencing the potential effects of microplastics following ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of microplastic pollution identified here (Fig. 7 ), based on mechanistic evidence of biological responses, are likely to apply to a wide range of marine life forms (e.g., both active and passive filter feeders, sessile predators and zooplankton feeders 7 , 43 , 71 ). Although the experimental conditions can only simulate natural conditions (where additional factors can interact to determine coral mortality), based on our findings we anticipate that, if microplastic contamination is not stopped, the values predicted for 2030–2060 will be, in many parts of the oceans similar or higher than those used in our experimental systems.…”
Section: Discussionmentioning
confidence: 90%